An introduction to group work practice - Toseland, Ronald W. (Pearson Education Limited, 2017)
Widely used by professionals, educators, and students in undergraduate and graduate courses in schools of social work throughout the United States and the world, this text presents a comprehensive, coherent, organized overview of group work practice from a generalist practice perspective. The new Eighth Edition continues to include typologies illustrating group work practice with task and treatment groups at the micro-, meso-, and macro-levels. Thoroughly updated throughout, the new edition of An Introduction to Group Work Practice includes research on virtual groups, updated and deeper content on practice with treatment and task groups, the most current literature on working with reluctant and resistant group members, updated and expanded sections on working with individuals who have difficulty engaging in and sustaining work in groups, updated material on leadership and diversity, and thoroughly updated reference material and new content from evidence-based practice sources.